2007
DOI: 10.1083/jcb.200611063
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of serine, threonine, or lysine residues on the cytoplasmic tail can induce ERAD of MHC-I by viral E3 ligase mK3

Abstract: The mechanism by which substrates for endoplasmic reticulum–associated degradation are retrotranslocated to the cytosol remains largely unknown, although ubiquitination is known to play a key role. The mouse γ-herpesvirus protein mK3 is a viral RING-CH–type E3 ligase that specifically targets nascent major histocompatibility complex I heavy chain (HC) for degradation, thus blocking the immune detection of virus-infected cells. To address the question of how HC is retrotranslocated and what role mK3 ligase play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
253
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(269 citation statements)
references
References 58 publications
(108 reference statements)
8
253
0
4
Order By: Relevance
“…7A and B). In this regard, several reports have previously demonstrated that nonlysine residues, including cysteines, serines and threonines, can also serve as ubiquitin acceptor sites or that ubiquitination can occur on the N-terminal residue of the substrate (11,14,41,83,88). Hence, we conclude that while Dok-1 lysine residues are major Dok-1 ubiquitylation sites, other nonlysine Dok-1 residues could also contribute to Dok-1 ubiquitination.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…7A and B). In this regard, several reports have previously demonstrated that nonlysine residues, including cysteines, serines and threonines, can also serve as ubiquitin acceptor sites or that ubiquitination can occur on the N-terminal residue of the substrate (11,14,41,83,88). Hence, we conclude that while Dok-1 lysine residues are major Dok-1 ubiquitylation sites, other nonlysine Dok-1 residues could also contribute to Dok-1 ubiquitination.…”
Section: Resultsmentioning
confidence: 78%
“…In general, proteins are targeted for proteasomal degradation by covalent attachment of polyubiquitin chains to their lysine residues, albeit other residues could also be involved (11,14,41,83,88). We found that proteasomal degradation of Dok-1 is largely mediated through ubiquitination of its lysine residues.…”
Section: Discussionmentioning
confidence: 82%
“…In a typical reaction, one of the at least 38 E2 enzymes interacts with activated ubiquitin and one of a near thousand E3 enzymes. The E3 then recognizes the target molecule and catalyzes the transfer of ubiquitin on a lysine or, less frequently, serine, cysteine, or threonine residues (1,(3)(4)(5). The E2/E3 combination and the localization of the complex confer the specificity to the reaction toward a given substrate (1,6).…”
mentioning
confidence: 99%
“…Similarly, recent work showed that polyubiquitin chains linked to a substrates cysteine are necessary for cargo translocation across the peroxisomal membranes [25][26][27] or can be formed during the process of chain-assembly for the formation of polyubiquitin chains [28][29][30]. Other groups reported the occasional modification of threonines and serine hydroxyl groups by polyubiquitin chains [29,31].…”
Section: Ubiquitin Signalsmentioning
confidence: 91%
“…Other groups reported the occasional modification of threonines and serine hydroxyl groups by polyubiquitin chains [29,31]. Ubiquitination on serine, threonine and cysteine has to be analyzed with modified proteomic methods because of the chemical nature of the ester linkage, which is subject to hydrolysis during the typical workflow of a proteomic experiment.…”
Section: Ubiquitin Signalsmentioning
confidence: 99%